2017
DOI: 10.1002/jbm.a.36193
|View full text |Cite
|
Sign up to set email alerts
|

Polyester vascular patches acquire arterial or venous identity depending on their environment

Abstract: Polyester is commonly used in vascular surgery for patch angioplasty and grafts. We hypothesized that polyester patches heal by infiltration of arterial or venous progenitor cells depending on the site of implantation. Polyester patches were implanted into the Wistar rat aorta or inferior vena cava and explanted on day 7 or 30. Neointima that formed on polyester patches was thicker in the venous environment compared to the amount that formed on patches in the arterial environment. Venous patches had more cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 73 publications
2
28
0
Order By: Relevance
“…9,10 Previously we showed that lymphocytes and macrophages accumulate in the neointima that forms on the luminal surface after patch angioplasty. 11,12 We also showed that lymphocytes and macrophages are present in the nascent neointima of a human vein graft. 13 Furthermore, macrophages and T cells induce neointimal hyperplasia in a mouse carotid artery injury model, 14,15 whereas depleting macrophages inhibits neointimal hyperplasia in a rabbit balloon injury model 16 ; we also showed that nanoparticles containing rapamycin that were conjugated to the pericardial patch decrease neointimal thickness and macrophage accumulation.…”
mentioning
confidence: 65%
“…9,10 Previously we showed that lymphocytes and macrophages accumulate in the neointima that forms on the luminal surface after patch angioplasty. 11,12 We also showed that lymphocytes and macrophages are present in the nascent neointima of a human vein graft. 13 Furthermore, macrophages and T cells induce neointimal hyperplasia in a mouse carotid artery injury model, 14,15 whereas depleting macrophages inhibits neointimal hyperplasia in a rabbit balloon injury model 16 ; we also showed that nanoparticles containing rapamycin that were conjugated to the pericardial patch decrease neointimal thickness and macrophage accumulation.…”
mentioning
confidence: 65%
“…Interestingly, in a rat model of polyester patches implanted into the aorta or inferior vena cava, polyester patches healed by infiltration of host arterial or venous progenitor cells depending on the site of implantation. Moreover, when these synthetic patches were treated with AVF, they would have decreased neointimal thickness with neointimal ECs expressing the arterial identity markers ephrin-B2 and Notch4, in addition to the venous identity markers Eph-B4 and COUP-TFII (dual arterial-venous identity) [60]. These data suggest that synthetic patches heal by acquisition of identity of their environment.…”
Section: Patch Angioplastymentioning
confidence: 88%
“…Venous patches additionally exposed to arterial flow also gain arterial identity, that is they gain dual arterial-venous identity, similar to arteriovenous fistulae ( Table II ). 10,12 These changes in identity occur in synthetic patches, suggesting that host cells infiltrating into the vascular patch determine vessel identity in these models. 12 It is interesting to speculate that manipulation of vascular patch identity may be possible, and if so, this may be a strategy to inhibit local development of neointimal hyperplasia.…”
Section: Clinical Applicationsmentioning
confidence: 94%